1996
DOI: 10.1021/js950477m
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Recombinant Human Erythropoietin in Liposomes in Rats: Influence of Lipid Composition and Size of Liposomes on Bioavailability

Abstract: Intestinal absorption of recombinant human erythropoietin (Epo) encapsulated in liposomes (Epo/liposomes) was examined by measuring the pharmacological effects of Epo after oral administration in rats. Circulating reticulocyte counts after oral administration of Epo/liposomes showed a profile different from that after intravenous administration. Epo/liposomes 0.1 micron in diameter were absorbed more effectively than those 0.2 micron in diameter. In the 0.1 micron Epo/liposomes composed of dipalmitoylphosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…This appearance is typical for discoid structures, because they are mainly adsorbed at their hydrophobic edges onto the copper grid (Gursky, 2002;Jayaraman et al, 2005;Mehta et al, 2003;Sevcsik et al, 2007Sevcsik et al, , 2008. Though rh-Epo containing vesicles were described as drug-delivery systems before, our observations showed, for the first time, that rh-Epo enables the transformation of liposomal membranes (Maitani et al, 1996(Maitani et al, , 1999Moriya et al, 1997). However, those drug-delivery experiments were performed with liposomes consisting of DPPC and various sterols.…”
Section: Resultssupporting
confidence: 51%
“…This appearance is typical for discoid structures, because they are mainly adsorbed at their hydrophobic edges onto the copper grid (Gursky, 2002;Jayaraman et al, 2005;Mehta et al, 2003;Sevcsik et al, 2007Sevcsik et al, , 2008. Though rh-Epo containing vesicles were described as drug-delivery systems before, our observations showed, for the first time, that rh-Epo enables the transformation of liposomal membranes (Maitani et al, 1996(Maitani et al, , 1999Moriya et al, 1997). However, those drug-delivery experiments were performed with liposomes consisting of DPPC and various sterols.…”
Section: Resultssupporting
confidence: 51%
“…Some studies have already demonstrated that liposomalization of therapeutic and cosmetic agents can enhance their activity by improving their stability and permeability as well as, giving targeting ability and controlling the release of entrapped agents. Some proteins, such as insulin, 14,15) calsitonin, 16,17) and erythropoietin, 18) which are can be digested and have low permeability through intestinal membrane, have been shown to improve their pharmacological effects through oral administration by various formulations of liposomes. We previously showed that oral administration of liposomal lactoferrin enhanced host immune ability and anti-inflammatory effects.…”
mentioning
confidence: 99%
“…Some studies have already demonstrated that liposomalization of therapeutic and cosmetic agents can enhance their activity by improving their stability and permeability, and also giving a targeting ability and time release. Some protein agents such as insulin, 25,26) calcitonin, 27,28) parathyroid hormone 28) and erythropoietin, 29) which are susceptible to being digested and also have low permeability for the intestinal membrane, have been shown to improve their pharmacological effects through oral administration by various liposomal applications. In this study, bLF is encapsulated into liposome consisting of egg yolk phosphatidylcholine (EPC) and phytosterol in order to orally administer bLF more effectively.…”
mentioning
confidence: 99%